Comparison of 2, 4-D, dicamba and halauxifen-methyl alone or in combination with glyphosate for preplant weed control. (18th February 2021) - Askew, M. Carter; Cahoon, Charles W.; York, Alan C.; Flessner, Michael L.; Langston, David B.; Ferebee, J. Harrison
Abstract: A field study was conducted in 2017 and 2018 to determine foliar efficacy of halauxifen-methyl, 2, 4-D, or dicamba applied alone and in combination with glyphosate at preplant burndown timing. Experiments were conducted near Painter, VA; Rocky Mount, NC; Jackson, NC; and Gates, NC. Control of horseweed, henbit, purple deadnettle, cutleaf evening primrose, curly dock, purple cudweed, and common chickweed were evaluated. Halauxifen-methyl applied at 5 g ae ha −1 controlled small and large horseweed 89% and 79%, respectively, and was similar to control by dicamba applied at 280 g ae ha −1 . Both rates of 2, 4-D—533 g ae ha −1 (low rate [LR]) or 1, 066 g ae ha −1 (high rate [HR])—were less effective than halauxifen-methyl and dicamba for controlling horseweed. Halauxifen-methyl was the only auxin herbicide to control henbit (90%) and purple deadnettle (99%). Cutleaf evening primrose was controlled 74% to 85%, 51%, and 4% by 2, 4-D, dicamba, and halauxifen-methyl, respectively. Dicamba and 2, 4-D controlled curly dock 59% to 70% and were more effective than halauxifen-methyl (5%). Auxin herbicides applied alone controlled purple cudweed and common chickweed 21% or less. With the exception of cutleaf evening primrose (35%) and curly dock (37%), glyphosate alone provided 95% or greater control of all weeds evaluated. These experiments demonstrate halauxifen-methyl effectively (≥79%) controls horseweed, henbit, and purple deadnettle, whereas common chickweed, curly dock, cutleaf evening primrose, and purple cudweed control by the herbicide is inadequate (≤7%).